2022
DOI: 10.1021/acssensors.2c00964
|View full text |Cite
|
Sign up to set email alerts
|

Turn-On Fluorescence Chemical Sensing through Transformation of Self-Trapped Exciton States at Room Temperature

Abstract: Most of the current fluorescence sensing materials belong to the turn-off type, which make it hard to detect toxic substances such as benzene, toluene, and xylene (BTX) due to the lack of active chemical sites, thereby limiting their development and practical use. Herein, we show a guest–host mechanism stemming from the confined emitter’s self-trapped exciton (STE) states or electron–phonon coupling to achieve turn-on fluorescence. We designed a luminescent guest@metal–organic framework (LG@MOF) composite mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…These results indicate that the extent of J-aggregation increases across the sequentially obtained four compounds (PyS-B → PyS-G → PyS-Y → PyS-R). 58–62 Furthermore, we performed concentration-dependent lifetime experiments for PyS-Y in an ethanol and toluene mixture (1 : 2), and observed that the excited state lifetime increased with increasing concentration (Fig. S22d, ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the extent of J-aggregation increases across the sequentially obtained four compounds (PyS-B → PyS-G → PyS-Y → PyS-R). 58–62 Furthermore, we performed concentration-dependent lifetime experiments for PyS-Y in an ethanol and toluene mixture (1 : 2), and observed that the excited state lifetime increased with increasing concentration (Fig. S22d, ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…34,35 Thus, there is a lack of luminescent sensing of such VOCs via the rare "turn-on" detection that eliminates the risk of faulty responses and avoids signal-to-noise ratio and is more applicable for onground detection. 6,36 Given the above background and significance, it is highly desirable to contribute to the underexplored Ni(II) MOFs as dual luminescent and electrochemical sensors. 37 (3), that are synthesized under environmentally-friendly, ambient conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In view of this scenario, handleable sensory probes are in demand for easy, prompt, and selective sensing of such VOCs. Although the luminescent sensing of such VOCs at the ppb level is a handful, all are based on the quenching (turn-off) mechanism. , Thus, there is a lack of luminescent sensing of such VOCs via the rare “turn-on” detection that eliminates the risk of faulty responses and avoids signal-to-noise ratio and is more applicable for on-ground detection. , …”
Section: Introductionmentioning
confidence: 99%
“…Organic small molecules have been studied extensively due to their many applications, such as in solar cells 7,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] and other fields. 2,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] These wide applications are due to their facile synthesis and versatile tuning ability to meet specific requirements. For instance, by covalently bonding three segments, we were able to construct an organic small molecule with cascade electronic energy levels in the format of D-A1-A2 31 or with delocalization for excitons 68 for solar cell applications.…”
Section: Introductionmentioning
confidence: 99%